Enhanced biosorption in a re-configured wastewater treatment process - Zhang Sheng (2015)
Abstract Biosorption in wastewater treatment process is described as the phenomenon where biomass uptakes carbonaceous substrates from the wastewater in a rapid manner. In this research, instead of a single physical-chemical phenomenon, biosorption is recognized as the combination of three sub mechanisms, including surface sorption, bioaccumulation and EPS entrapment. Both overall biosorption performances as well as the contribution from each sub mechanism were investigated with respect to biomass surface area; biomass surface charge as well as biomass EPS production. Three types of biomass (e.g. activated sludge, anaerobic sludge and glycogen accumulating organism (GAO)) was employed for the investigation. Lab data suggested that GAO demonstrated much more substantial biosorption capacity than other two biomass did and was strongly recommended for the potential industrial application. Investigation on biosorption enhancement was also conducted. Two possible approaches were proposed: 1. Enhanced biosorption by glycogen accumulating organism (GAO); 2. Enhanced biosorption by normal activated sludge via process manipulation. For the second approach, following parameters were selected for process manipulation purpose: F/M ratio; dissolved oxygen level; sludge retention time and pH (short term). The experiment data shows that GAO delivered the best overall performance ranging from 45.77 to 56.48 mg COD/g SS at the pH range between 6 to 8, as compared with the performance of aerobic sludge (from 26.54 to 30. 27 mg COD/g SS) as well as the performance of anaerobic sludge (from 24.31 to 27.82 mg COD/g SS). It is also suggested that biosorption generally delivers the best performance when activated sludge was cultivated under low F/M and long SRT conditions. At such conditions, activated sludge delivered an overall biosorption capacity of 57.2 mg COD/g SS at pH=7 and 59.8 mg COD/g SS at pH=8. In addition, a re-configured wastewater treatment process is subsequently proposed to exploit the biosorption phenomenon. Through enhanced biosorption, the proposed re-configured process is anticipated to achieve smaller carbon footprint by concentrating organic substrate in the biosorption tank with biomass cultivated under specific conditions and thereafter have this carbon-rich biomass bypass the typical activated sludge process (aeration stage) to flow directly into anaerobic digesters for methane generation. This research also highlighted that influent wastewater characteristics in terms of particulate, colloidal, and dissolved carbonaceous materials, shall need to be taken into consideration when choosing the suitable operating conditions for preparing the biomass for biosorption.